Massacres : bioarchaeology and forensic anthropology approaches - Anderson, Cheryl P.; Martin, Debra L.; Larsen, Clark Spencer (Bioarchaeological interpretations of the human past., 2018)
The goal of this edited volume is to present case studies that integrate the evidence from human remains with the broader cultural and historical context through the utilization of social theory to provide a framework for interpretation. This volume highlights case studies of massacres across time and space that stress innovative theoretical models that help make sense of this unique form of violence. The primary focus will be on how massacres are used as a strategy of violence across time and cultural/geopolitical landscapes.